Melancholic depression. A hermeneutic phenomenological account - Francesca Brencio; Valeria Bizzari (Rivista Internazionale di Filosofia e Psicologia, 2022)
The overarching aim of this paper is to provide a comprehensive account of melancholic depression from the perspective of hermeneutic phenomenology. More specifically, we propose that this condition should be interpreted as an alteration in the intentional arc that affects corporeality, temporality, and spatiality, rather than as a mood disorder. In fact, classifying melancholic depression as a mood disorder seems a particularly poor choice; the mood disorder is not a cause but a consequence of a primary disturbance in operative intentionality. Our paper comprises four sections: (1) We provide a methodological and conceptual framework for our theoretical work, adopting a hermeneutic phenomenological perspective on melancholic depression, and underlining the main differences between melancholia and depression. (2) We offer a detailed reconstruction of the different interpretations of melancholic depression and their relationships to the issue of temporality. (3) We analyze the disruption of intentionality in melancholic depression and how it affects corporeality and directionality. (4) We focus on the disruption of moods and affects in melancholic depression, observing how they shape subjective experience. The goal of this theoretical contribution is to underscore the role of operative intentionality and its disruptions in melancholic depression. We argue that taking elements such as intentionality, embodiment, and spatiality into consideration could help to direct therapies along more promising paths.